Development of Project-Based Learning E-Modules with Authentic Evaluation to Improve Marketing Skills and Abilities in Higher Education - Desi Budiono; Lilian Mega Puri; Siti Suprihatin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Marketing skills and adaptability are critical competencies in 21st-century higher education, particularly within entrepreneurship learning. However, conventional learning approaches often lack contextual relevance and fail to foster these essential skills. This study aims to develop a Project-Based Learning (PJBL) e-module integrated with authentic evaluation to improve students’ marketing competencies and adaptability. This research employed the Research and Development (RD) method using the ADDIE model, involving stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation, student and lecturer questionnaires, observations, and tests. The subjects included 6 expert validators, 2 lecturers, and 60 students from an Economics Education program. Data analysis involved qualitative thematic interpretation and quantitative tests (T-test and N-Gain) using SPSS 25. Validation showed the e-module to be highly valid (average score = 4.05) and very practical (average score = 4.09). T-test results indicated a significant improvement (p 0.05) in students’ learning outcomes. The N-Gain score was 0.572 (58.88%), categorized as moderately effective in enhancing marketing skills and adaptability. The developed PJBL e-module with authentic evaluation supports interactive, contextual learning and aligns with 21st-century competencies. Its effectiveness indicates potential for broader implementation in similar courses to enhance entrepreneurial readiness and adaptive learning.